Prognosis of Pregnancy in Epileptics in Benin: A Case–Control Study - Thierry Adoukonou (Journal of Neurosciences in Rural Practice, 2020)
Objective The main purpose of this article is to define prognosis of pregnancies in epileptic women in Benin. Methods This was a case–control study that included 54 epileptic women who had at least one pregnancy matched to 162 controls on age, pregnancy term, and monitoring center. Information about epilepsy, treatment, pregnancy, and childbirth were collected. A logistic regression with odds ratio (OR) calculation was used to study the association. Results During pregnancy 22.22% of epileptic women experienced an increase in seizure frequency. Epileptics had more frequent miscarriages (OR: 1.84 [1.01–3.51]), more incidents during pregnancy (OR: 4.03 [1.04–15.60]), and were more often hospitalized (OR: 3.35 [1.46–7.69]) than women without epilepsy. They, more often, had premature children before 37 weeks of amenorrhea (OR: 2.10 [1.12–3.91]) and gave birth to low-birth-weight children (OR = 2.17 [1.00–4.76]). Conclusion Occurrence of a pregnancy in an epileptic woman in Benin is at risk and requires multidisciplinary monitoring by both neurologist and obstetrician to reduce complications.